2008
DOI: 10.1038/gene.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive association study of genetic variants in the IL-1 gene family in systemic juvenile idiopathic arthritis

Abstract: Patients with systemic juvenile idiopathic arthritis (sJIA) have a characteristic daily spiking fever and elevated levels of inflammatory cytokines. Members of the interleukin-1 (IL-1) gene family have been implicated in various inflammatory and autoimmune diseases, and treatment with the IL-1 receptor antagonist, Anakinra, shows remarkable improvement in some patients. This work describes the most comprehensive investigation to date of the involvement of the IL-1 gene family in sJIA. A two-stage case-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 48 publications
1
30
2
4
Order By: Relevance
“…Polymorphisms have been described in genes encoding innate immunity-associated factors and cytokines, such as IL-6, IL-1a, IL1-RN, macrophage inhibitory factor (MIF), or TNF in patients with sJIA [28][29][30] and IL-18, or MIF in patients with AOSD [31,32]. Loss-of-function variants in P2RX7, which encodes an ATP receptor that regulates IL-1 processing and secretion, have also been reported [33].…”
Section: Geneticsmentioning
confidence: 97%
“…Polymorphisms have been described in genes encoding innate immunity-associated factors and cytokines, such as IL-6, IL-1a, IL1-RN, macrophage inhibitory factor (MIF), or TNF in patients with sJIA [28][29][30] and IL-18, or MIF in patients with AOSD [31,32]. Loss-of-function variants in P2RX7, which encodes an ATP receptor that regulates IL-1 processing and secretion, have also been reported [33].…”
Section: Geneticsmentioning
confidence: 97%
“…6 Meta-analysis of the risk for systemic juvenile idiopathic arthritis showed that three IL-1 gene cluster SNPs (rs6712572, rs2071374, and rs1688075) and one IL-1 receptor cluster SNP (rs12712122) are associated with disease. 7 The genetic susceptibility for ankylosing spondylitis may be associated with the IL1A gene polymorphisms. 8 According to meta-analysis the following polymorphisms in the IL-1 gene cluster contribute to increased risk: IL-1RN (VNTR), IL-1A (rs1800587), and IL36B (rs1900287), with a distinct discrepancy for these associations among races.…”
Section: Asthma Osteoarthritis Autoimmune Diseasesmentioning
confidence: 99%
“…Es wurden jedoch eine gesteigerte Aktivierung von Inflammasomen und eine daraus resultierende gesteigerte Sekretion von IL-1β und abhängigen Zytokinen (IL-6, TNF-α) beschrieben [76][77][78]. Die gut dokumentierte Assoziation mit Punktmutationen in regulatorischen Regionen IL-1-assoziierter Gene, weiterer proinflammatorischer Gene (IL-6, TNF) sowie dem IL-10-Promoter (aber auch vielen anderen Genen) deutet auf eine genetische Komponente in der Pathophysiologie hin [79][80][81][82][83]. Letztendlich könnte die Akkumulation verschiedener genomischer Varianten zu einem Ungleichgewicht zwischen Caspase-1-abhängigen proinflammatorischen Botenstoffen und antiinflammatorischen Regulatoren führen und Entzündungs-prozesse bei der sJIA auslösen und/oder unterhalten [70].…”
Section: Caspase-1-abhängige Signalwege Im Kontext Rheumatischer Erkrunclassified